The fabrication of highly conductive and flexible Ag patterning through baking Ag nanosphere−nanoplate hybrid ink at a low temperature of 100 °C. (12th February 2018) - Han, Y D; Zhang, S M; Jing, H Y; Wei, J; Bu, F H; Zhao, L; Lv, X Q; Xu, L Y
Abstract: With the aim of developing highly conductive ink for flexible electronics on heat-sensitive substrates, Ag nanospheres and nanoplates were mixed to synthesize hybrid inks. Five kinds of hybrid ink and two types of pure ink were written to square shape on Epson photo paper using rollerball pens, and sintered at a low temperature (100 °C). The microstructure, electrical resistivity, surface porosity, hardness and flexibility of silver patterns were systematically investigated and compared. It was observed that the optimal mixing ratio of nanospheres and nanoplates was 1:1, which equipped the directly written pattern with excellent electrical and mechanical properties. The electrical resistivity was 0.103 μ Ω · m, only 6.5 times that of bulk silver. The enhancement compared to pure silver nanospheres or nanoplates based ink was due to the combined action of nanospheres and nanoplates. This demonstrates a valuable way to prepare Ag nanoink with good performance for printed/written electronics.